The Role of the Abbasid Dynasty in Building Scientific Infrastructure: A Study of Classical Islamic Educational Institutions - Ngatmin Abbas; Mukhlis Fathurrohman; Edy Muslimin (Jurnal Kawakib, 2025)
The Abbasid Dynasty period is recognized as the golden age of Islamic civilization, during which knowledge flourished rapidly. This research aims to historically examine the role of the Abbasid Dynasty in building scientific infrastructure through the establishment and development of classical Islamic educational institutions. This study employs a qualitative methodology with a historical approach and document analysis. Data were obtained through a literature review of primary and secondary sources relevant to intellectual dynamics and educational institutions during the Abbasid period. The findings indicate that the Abbasid Dynasty, through the support of caliphs such as Harun al-Rashid and Al-Ma'mun, not only established institutions like Bayt al-Hikma (House of Wisdom) and madrasas, but also created supporting systems including patronage, budgeting, and expanded access to knowledge. It was also discovered that this period became a milestone for integration between religious and rational sciences, giving birth to an open and tolerant academic culture. The implications of this research demonstrate that many contemporary Islamic educational structures, such as university systems and integrated curricula, are rooted in the Abbasid educational model. This research provides an important contribution to the development of Islamic Religious Education studies, particularly in building holistic and historical educational models.